Bronze and Sunflower - Cao, Wenxuan, 1954- (Candlewick Press, 2019)
Taken in by a poor family in a rural village after the death of her father, Sunflower bonds with the family's only child, Bronze, who has not spoken since being traumatized by a terrible fire.